Germination of psychrotolerant clostridia responsible for red meat spoilage : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Technology at Massey University, Palmerston North, New Zealand - Adam, Katharine Helen (Massey University, 2012)
Psychrotolerant clostridia are responsible for spoilage of fresh chilled vacuum-packed red meat (beef, lamb and venison). Red meat is one of New Zealand’s primary exports, and spoilage results in financial loss. Spoilage by psychrotolerant clostridia is difficult to control due to the ability of these bacteria to grow at cold temperatures, down to -1.5 °C. They can also form spores that have increased resistance to heat, chemicals, oxygen and desiccation compared to vegetative bacterial cells. As clostridia are strict anaerobes, it is considered highly likely that initial contamination of meat is primarily with spores. The main objective of this work was to determine the triggers of germination of spores, of those psychrophilic and psychrotrophic clostridia, associated with spoilage of New Zealand red meat. Germination of psychrotolerant clostridia was studied using a range of techniques including molecular, in vitro, and on meat methods. In this study in vitro germinant systems were identified for Clostridium frigidicarnis, and a New Zealand species designated LA1, consisting of lactate in combination with an amino acid. Some of the amino acids identified, including valine and cysteine, are naturally present on the surface of red meat. Failure to chill to, or maintain meat at, the recommended temperature, of -1.5 °C and a pH of above 5.5 were identified as being important factors leading to spoilage by Cl. frigidicarnis. Germination in Clostridium estertheticum was extremely poor in media, compared with meat slurry or fresh meat, preventing the identification of a specific germinant system(s), and indicating a non-nutrient factor may be involved. Two distinct nonchemical interventions, hot water wash (HWW) and cold water wash (CWW), were found to reduce spoilage of vacuum-packed chilled lamb inoculated with spores of Cl. estertheticum. Vegetative cells of psychrotolerant clostridia survived exposure to air longer than expected, upwards of seven days in the case of Cl. estertheticum subsp. estertheticum, suggesting that they play a greater role in initial contamination of meat than originally thought. From an industry point of view the results highlight the importance of preventing initial contamination and proper chilling, as well as the need for further investigation of HWW and CWW interventions.
Content removed from appendix 8 for copyright reasons: Adam, K.H., Flint, S.H., & Brightwell, G. (2010). Psychrophilic and psychrotrophic clostridia: Sporulation and germination processes and their role in the spoilage of chilled, vacuum-packaged beef, lamb and venison. International Journal of Food Science & Technology, 45, 1539-1544. doi:10.1111/j.1365-2621.2010.02320.x. Adam, K.H., Brunt, J., Brightwell, G., Flint, S.H., & Peck, M.W. (2011). Spore germination of the psychrotolerant, red meat spoiler, Clostridium frigidicarnis. Letters in Applied Microbiology, 53, 92-97. doi:10.1111/j.1472-765X.2011.03071.x. Adam, K.H., Flint, S.H., & Brightwell, G. (2013). Reduction of spoilage of chilled vacuum-packed lamb by psychrotolerant clostridia. Meat Science, 93(2), 310-315. doi:10.1016/j.meatsci.2012.09.011
Keywords: Clostridium; Clostridia; Meat hygiene; Bacterial spores; Germination; Food contamination; Clostridium frigidicarnis; Clostridium estertheticum